URBAN LAND-USE AND EFFECT ON DEVELOPMENT IN OSOGBO METROPOLIS - BASSEY, MOSES (IJRDO - Journal of Social Science and Humanities Research, 2020)
Globally, land is used for different purposes. These are but not limited to: residential, commercial, religious, recreational, industrial, transport etc. The proportion of land allocated to various use in different parts of the world vary tremendously depending on the level of development, compliance with the planning regulations and the purpose to which the land is to put (United Nations Environmental Project, 1999). Osun state was created in 1991 with its capital in Osogbo, the need to develop the town to befit the status of a state capital made the government formulate different development policies. These policies led to high rate of rural-urban migration because of the increased in socio-economic activities and a high demand for land in the metropolis. This paper therefore analyzed urban land-use pattern and its effect on development in Osogbo. The study used descriptive survey research design; the stratified sampling technique was used to purposively drawn 250 respondents in the study area to participate in the study. The study relied extensively on both primary and secondary sources of data. The primary sources were 250 questionnaires administered and five Key-Informant Interviews conducted while the secondary data were: books, journals, online materials, newspapers and archival materials. The findings from research question two revealed that 23.6% of the respondents agreed that improper land-use increased natural disaster within the metropolis. 35.2% of the respondents agreed that it increases pressure on the available social amenities because of congestion while 19.6% agreed that it leads to in environmental degradation. The study therefore concluded that the pattern of land-use in Osogbo was hampering development and recommended that there is a need to redesign the Master Plan of the city and ensure compliance to the planning regulations in order to achieve optimum development.